An analysis of Higher Education in the Northern Region of Brazil (Research, Society and Development, 2022)
The advent of the process and globalization increasingly suggests the need to value knowledge, making innovations, as well as scientific and technological development, establish themselves as primary ways of guaranteeing participation in this new reality. In this way, countries around the world seek to promote changes in their educational systems, inserting themselves in a multifaceted process of diversification of higher education that has been necessary. Thus, a process of internationalization of higher education as a central theme in higher education institutions, causing universities to strive to expand their frontiers of knowledge in order to consolidate ties, where they will remain imbued with the responsibility of presenting concrete responses to society. The methodology used in writing the article was based on data collection carried out through Google Scholar virtual libraries; LILACS; BIREME AND VHL, where the descriptors used were: “Higher education”; "North region"; “Universities”, in Portuguese; English and Spanish, where the descriptors were previously selected, in addition to being variously combined and crossed, where the following inclusion criteria were considered: articles available in full, published between 2010 and 2021; in Portuguese, English and Spanish; and as exclusion criteria: articles that were not compatible with the object of study and articles not available with free access. Thus, it was possible to present a historical line carrying out an analysis of the evolution of higher education in the northern region, offering subsidies for future studies on the subject of this article to be deepened, in order to identify and adapt to the new demands of training professionals.